How do physiological responses such as respiratory frequency, heart rate, and galvanic skin response (GSR) change under emotional stress? - Civitello, Diana; Finn, Dan; Flood, Monica; Salievski, Erbay; Schwarz, Marisa; Storck, Zoe (Journal of Advanced Student Sciences (JASS), 2014)
The human body exhibits different physiological responses to stress. One of these stressful situations includes when one is made uncomfortable or is possibly being deceitful, which is the physiological response that we were interested in measuring. In order to measure these changes, we devised an experiment in which we first asked participants ten baseline questions followed by ten experimental questions. We analyzed changes in galvanic skin response, heart rate, and respiratory frequency between the two sets of questions. The experimental questions were personal and potentially stress-inducing, intending to make the participant feel uncomfortable and stressed (the participants signed a waiver and were not harmed, nor was any personal information disclosed or recorded). We conducted this experiment on thirty participants, measuring these three physiological conditions before and while we asked them both sets of questions. We compared the measurements of the first ten control questions with the second ten experimental questions and found the mean and mean percent change of each. The pvalues obtained from our data were as follows: galvanic skin response p=0.0029, heart rate p=0.69, and respiratory frequency p=0.00024. These results imply that the galvanic skin response significantly increased while respiratory frequency significantly decreased when participants were put under stress. The change in heart rate was not statistically significant. While the GSR results supported our hypothesis, the heart rate and respiratory frequency measurements did not. We believe our participants may have felt nervous, anxious, or stressed when we initially started conducting the experiment, skewing our heart rate and respiratory frequency control measurements. Another possible explanation is a physiological compensatory mechanism in response to stress. In order to counteract emotional stress, it is possible that respiratory frequency was decreased in an attempt to increase expiration time and increase acetylcholine release on the cardiac muscle, thereby decreasing unnecessary cardiac output.
An article that appeared in JASS, issue 2014
Keywords: ECG; GSR; emotion; stress